2021
DOI: 10.1186/s13148-021-01159-6
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-dependent MALAT1 delocalization drives c-Myc induction in thymic epithelial tumors

Abstract: Background Thymic epithelial tumors (TETs) are rare neoplasms, originating from epithelial thymic cells. The oncogenic potential of these rare neoplasms is still largely undefined, and a deeper molecular characterization could result in a relevant advance in their management, greatly improving diagnosis, prognosis and treatment choice. Deregulation of N6-methyladenosine (m6A) RNA modification, catalyzed by the METTL3/METTL14 methyltransferase complex, is emerging as a relevant event in cell dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…In addition, the MALAT1 expression level is negatively correlated with the survival rate in cancer patients 28 . MALAT1 induces cell proliferation and metastasis via the MAPK/ERK and PI3K/AKT signaling pathways in retinoblastoma and ovarian cancer, respectively 29 , 30 , and it is known to enable the high expression of the key oncogene MYC in thymic epithelial tumors 31 . Interestingly, in HepG2 cells, MALAT1 was also found in mitochondria, and its knockdown limited ATP synthesis and tumor cell invasion 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the MALAT1 expression level is negatively correlated with the survival rate in cancer patients 28 . MALAT1 induces cell proliferation and metastasis via the MAPK/ERK and PI3K/AKT signaling pathways in retinoblastoma and ovarian cancer, respectively 29 , 30 , and it is known to enable the high expression of the key oncogene MYC in thymic epithelial tumors 31 . Interestingly, in HepG2 cells, MALAT1 was also found in mitochondria, and its knockdown limited ATP synthesis and tumor cell invasion 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Iaiza et al found that the methyltransferase METTL3 is overexpressed in TEN and responsible for the induction of c-MYC expression through methylation and delocalization of the lncRNA MALAT1. Silencing of METTL3 combined with cisplatin or c-MYC inhibitor promotes apoptosis in TEN cells [ 49 ]. Bisulfite pyrosequencing in 46 TEN and 20 paired thymus tissues revealed higher promoter methylation of G protein subunit gamma 4 (GNG4), growth hormone secretagogue receptor (GHSR), homeobox D9 (HOXD9) and spalt like transcription factor 3 (SALL3) in TC than in thymoma.…”
Section: Alterations Of Dna Methylation In Tensmentioning
confidence: 99%
“…METTL3 in human tissue is highly expressed and conserved, especially in the testes. Recent studies reported that METTL3 is significantly highly expressed in chronic myeloid leukemia ( Ianniello et al, 2021 ), thymic epithelial tumors ( Iaiza et al, 2021 ), esophageal cancer ( Han et al, 2021 ), and prostate cancer ( Chen et al, 2021b ), suggesting a close relationship with malignant tumor development. Previous studies also suggested that METTL3 is significantly up-regulated in BC.…”
Section: M6a Roles and Mechanisms In Bcmentioning
confidence: 99%